2006
DOI: 10.1080/08035250600760790
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal behaviour characteristics and psychological problems at 6 years

Abstract: These findings suggest that the NBAS could be useful for identifying neonates at risk of later psychological problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…The long term consequences of abnormal neonatal behavior is understudied. However, there is evidence linking neonatal behavior to infant temperament (Tirosh et al, 1992), childhood behavioral problems (Ohgi et al, 2003; Canals et al, 2006) and developmental disabilities (Ohgi et al, 2003) . Therefore, the long-term implications of our findings are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The long term consequences of abnormal neonatal behavior is understudied. However, there is evidence linking neonatal behavior to infant temperament (Tirosh et al, 1992), childhood behavioral problems (Ohgi et al, 2003; Canals et al, 2006) and developmental disabilities (Ohgi et al, 2003) . Therefore, the long-term implications of our findings are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Premature and low birth weight infants are at risk for developing behavior problems, including regulatory, attention, internalizing, and externalizing problems during later infancy, toddlerhood, and childhood [16,17]. Newborn behavioral characteristics, such as poor motor performance, low orientation, and low state regulation, have also been associated with psychological problems in childhood [18,19].…”
Section: Fetal and Neonatal Developmentmentioning
confidence: 97%
“…Like the NNNS, the NBAS demonstrates significant associations with the CBCL 44,45 and the SDQ 46 at follow-up. Canals, Esparo and Fernandez-Ballart 44 examined the extent to which clusters of the NBAS, administered at ages 3 days and 4 weeks old in healthy infants ( n =80), predicted CBCL Internalizing and Externalizing Problem scores at age 6 years.…”
Section: Introductionmentioning
confidence: 94%
“…Canals, Esparo and Fernandez-Ballart 44 examined the extent to which clusters of the NBAS, administered at ages 3 days and 4 weeks old in healthy infants ( n =80), predicted CBCL Internalizing and Externalizing Problem scores at age 6 years. Findings showed that lower Orientation and higher Motor and Habituation cluster scores on day 3 of life predicted externalizing outcomes, whereas lower Habituation cluster scores at age 4 weeks predicted internalizing outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation